Insan Kamil Sebagai Basis Pengembangan Kreativitas Dalam Pendidikan Islam - Kholid Mawardi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: This paper intends to try to describe the conception of creativity in Islamic education. Islamic education has the ultimate goal the establishment of perfect man, be a basis for the development of creativity of learners. The emergence of the creative potential of the students into the formation conditions perfect man. To bring creativity perfect man based paradigm is needed that can lead to the creativity of the students, the educational paradigm approach to creativity is a critical educational paradigm that aims to prevent students from dehumanization, the model of the problem facing critical educational paradigm is able to foster the creativity of the students.